2021
DOI: 10.1016/j.ebiom.2021.103498
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative circulating tumour DNA is associated with pathologic response and recurrence-free survival after resection of colorectal cancer liver metastases

Abstract: Background Recurrence rates after resection of colorectal cancer liver metastases (CRLM) are high and correlate with worse survival. Postoperative circulating tumour DNA (ctDNA) is a promising prognostic biomarker. Focusing on patients with resected CRLM, this study aimed to evaluate the association between the detection of postoperative ctDNA, pathologic response and recurrence-free survival (RFS). Methods Twenty-three patients were selected from an ongoing phase-3 tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 52 publications
(81 reference statements)
1
33
0
Order By: Relevance
“…As the MT strategies were the same, the difference to our results likely reflects the rigor with which our ST‐ddPCR analyses were conducted. In contrast to the Loupakis study, and several other studies using ddPCR for ctDNA detection [ 28 , 36 , 37 , 38 ], our targets were carefully selected from WES data after a thorough clonality assessment. While the addition of WES prior to ST analysis increases costs, including it minimizes the risk of tracking a subclonal and noninformative variant.…”
Section: Discussionmentioning
confidence: 99%
“…As the MT strategies were the same, the difference to our results likely reflects the rigor with which our ST‐ddPCR analyses were conducted. In contrast to the Loupakis study, and several other studies using ddPCR for ctDNA detection [ 28 , 36 , 37 , 38 ], our targets were carefully selected from WES data after a thorough clonality assessment. While the addition of WES prior to ST analysis increases costs, including it minimizes the risk of tracking a subclonal and noninformative variant.…”
Section: Discussionmentioning
confidence: 99%
“…18 Meta-analysis of the association between postablation circulating DNA and RFS included 10 eligible studies. 2,23,25,[27][28][29]31,34,35,36 Circulating DNA above the cutoff in a post-ablation sample was associated with a shorter RFS (pooled HR = 4.5, 95% CI 3.4-6.1, n = 569) (Figure 4(c)), and the funnel plots indicated no major publication bias (Supplemental Figure 2). Minimal heterogeneity was observed (χ 2 = 10.5, df = 10, p = 0.31, I 2 = 28.5%).…”
Section: Post-ablation Circulating Dna and Outcomementioning
confidence: 96%
“…27 The analytical methods used included polymerase chain reaction (PCR) based methods (e.g., BEAMing, ddPCR) (n = 13/28), 2,12,14,19,20,[28][29][30][31][32]35,37,39 targeted sequencing (n = 11/28), 17,18,[21][22][23][24][25][26][27]33,36 direct fluorescent assay (DFA) (n = 2/28), 38,15 mass spectrometry (n = 1/28), 40 or combined PCR and targeted sequencing (n = 1/28). 34 The majority of studies chose a tumor-agnostic marker of ctDNA, that is, assays covering mutations in RAS/BRAF (n = 6/28), 2,12,20,30,35,40 large gene panels covering various numbers of genes (n = 6/28), 21,22,25,26,33,36 or epigenetic markers (n = 2/28). 29,27 Less frequently a tumor-informed approach was applied (n = 7/28) 14,23,24,…”
Section: Tablementioning
confidence: 99%
“…Kobayashi et al showed that patients with resectable CRCLM who had preoperative detectable ctDNA in their plasma had statistically lower DFS and a tendency to have lower OS [ 71 ]. Achieving undetectable levels of ctDNA after CRCLM resection seems also to be associated with better DFS and a good pathological response to neoadjuvant chemotherapy [ 63 , 72 , 73 ]. Tie at al observed a 40-fold decrease in mutated ctDNA levels after neoadjuvant chemotherapy.…”
Section: The Impact Of the Molecular Profile On Follow-upmentioning
confidence: 99%